Smart responsive in situ hydrogel systems applied in bone tissue engineering - Wu, Shunli; Gai, Tingting; Chen, Jie; Chen, Xiguang; Chen, Weikai (Frontiers in Bioengineering and Biotechnology, 2024)
The repair of irregular bone tissue suffers severe clinical problems due to the scarcity of an appropriate therapeutic carrier that can match dynamic and complex bone damage. Fortunately, stimuli-responsive in situ hydrogel systems that are triggered by a special microenvironment could be an ideal method of regenerating bone tissue because of the injectability, in situ gelatin, and spatiotemporally tunable drug release. Herein, we introduce the two main stimulus-response approaches, exogenous and endogenous, to forming in situ hydrogels in bone tissue engineering. First, we summarize specific and distinct responses to an extensive range of external stimuli (e.g., ultraviolet, near-infrared, ultrasound, etc.) to form in situ hydrogels created from biocompatible materials modified by various functional groups or hybrid functional nanoparticles. Furthermore, “smart” hydrogels, which respond to endogenous physiological or environmental stimuli (e.g., temperature, pH, enzyme, etc.), can achieve in situ gelation by one injection in vivo without additional intervention. Moreover, the mild chemistry response-mediated in situ hydrogel systems also offer fascinating prospects in bone tissue engineering, such as a Diels–Alder, Michael addition, thiol-Michael addition, and Schiff reactions, etc. The recent developments and challenges of various smart in situ hydrogels and their application to drug administration and bone tissue engineering are discussed in this review. It is anticipated that advanced strategies and innovative ideas of in situ hydrogels will be exploited in the clinical field and increase the quality of life for patients with bone damage.